Diseño de una estación automatizada para la desinfección y toma de temperatura con miras a disminuir el riesgo de contagio del Covid-19 en las personas que ingresan a la UAN sede Cartagena (2021)
The main objetive of this project is to design and implement an an automated liquid for the disinfection and the taking of temperature where it can implement the current legislation for the electricity supplies and the design of the mechanical component; lastly, people prevent thus the spread of Covid-19 that enter to the university of Antonio Nariño installations headquarters Cartagena. With this project looks for existing a disinfection system and the taking of the temperature to mitigate the level of contagion of the disease Covid-19 inside the university of Antonio Nariño headquarters Cartagena, this will achieve to integrate electromechanical components to create an automated liquid that allows the university to comply with biosecurity protocols aforementioned in the 2020 resolution 666 (biosecurity general protocol Covid-19).